2021
DOI: 10.1111/jfbc.13770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different cooking methods on volatile flavor compounds of chicken breast

Abstract: Chicken is one of the highest selling meats worldwide. Different cooking methods produce various flavor compounds in cooked chicken, which affect consumers’ food choices. In this study, the volatile flavor components of Gushi chicken breast after stewing and air frying were detected using gas chromatography‐ion mobility chromatography (GC‐IMS) and principal component analysis (PCA), and the relative odor activity value (ROAV) was determined using PCA. A total of 43 volatile substances were identified. 3‐(methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Therefore, it plays a key role in the flavor perception of chicken soup ( Qi et al, 2017 ). (E)-hept-2-enal-M, phenylacetaldehyde, and valeraldehyde are important modifiers of overall flavor in braised and fried chicken ( Bi et al, 2021 ). Previous studies have shown that hexanal and 1-octen-3-ol are the main VOCs in Jingxing Yellow chicken, Tiannong Partridge chicken, and Wenchang chicken, confirming the main aroma VOCs in chicken, which provides a basis for breeding birds with improved meat flavor ( Jin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it plays a key role in the flavor perception of chicken soup ( Qi et al, 2017 ). (E)-hept-2-enal-M, phenylacetaldehyde, and valeraldehyde are important modifiers of overall flavor in braised and fried chicken ( Bi et al, 2021 ). Previous studies have shown that hexanal and 1-octen-3-ol are the main VOCs in Jingxing Yellow chicken, Tiannong Partridge chicken, and Wenchang chicken, confirming the main aroma VOCs in chicken, which provides a basis for breeding birds with improved meat flavor ( Jin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on of identification VOCs ( Fan et al, 2018 ; Xu et al, 2020 ; Bi et al, 2021 ; Jin et al, 2021 ). However, the intermediate metabolites of VOCs remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold in ROAV calculation was selected by olfactory thresholds in water taken from the literature ( 20 ). Compounds with ROAVs equal to or greater than 1 were actually the main flavor components of the analyzed samples, and compounds with ROAVs greater than 0.1 and less than 1 play a embellish role in aroma ( 21 ). The components that contribute most to the total flavor of a solid peach sample were defined as follows:…”
Section: Methodsmentioning
confidence: 99%
“…"Yuanmeng" clustered in one group with (E)-2-octenal (6), non-anal (9), and (E,E)-2,6-non-adienal (14). "Yulu" clustered with heptanoic acid (38), eugenol (39), and hexanal (40) individually, and also "Yuandong" clustered with β-ionone (17) and linalool (21). The remaining seven peaches "Baifeng, " "Wanhujing, " "Yihe, " "Jinxiu, " "Jinyuan, " "Huangguifei, " and "Ruipan-19" were clustered with γ-dodecalactone (23), (E)-β-ionone ( 24), dihydro-β-ionone (25), etc.…”
Section: Principal Component Analysis Based On Gas Chromatography-mas...mentioning
confidence: 99%
“…With the development of science and technology, from the initial sensory analysis to further qualitative and quantitative analyses of flavor components, mushrooms’ flavors have come to be more deeply studied. However, studies on the flavors of mushrooms after cooking are limited compared to those on the flavors of broth made from animal materials, such as Chinese Piao chicken meat [ 18 ], chicken breast [ 19 ] and squid mantle muscle [ 20 ]. Moreover, there has been no extensive investigation into the effect of different cooking methods on different LEs’ nutrient and flavor characteristics, which will further influence the product.…”
Section: Introductionmentioning
confidence: 99%